An Electrochemical Method for Measuring Localized Corrosion under Cathodic Protection. (12th November 2014) - Varela, F.; Tan, M. Y. J.; Forsyth, M.
Abstract : A new method has been developed to measure metal corrosion rates and their distribution under cathodic protection (CP). This method uses an electrochemically integrated multi-electrode array to take local measurements of cathodic current density while simulating a continuous metallic surface. The distribution of cathodic current densities obtained under CP was analyzed to estimate the anodic current component at each electrode of the array. Corrosion patterns determined by this new method have shown good correlation with visual inspection and surface profilometry of the multi-electrode array surface.